larvalign: Aligning Gene Expression Patterns from the Larval Brain of Drosophila melanogaster - Muenzing, Sascha E. A.; Strauch, Martin; Truman, James W.; Buehler, Katja; Thum, Andreas S.; Merhof, Dorit (Neuroinformatics, 2018)
The larval brain of the fruit fly Drosophila melanogaster is a small, tractable model system for neuroscience. Genes for fluorescent marker proteins can be expressed in defined, spatially restricted neuron populations. Here, we introduce the methods for 1) generating a standard template of the larval central nervous system (CNS), 2) spatial mapping of expression patterns from different larvae into a reference space defined by the standard template. We provide a manually annotated gold standard that serves for evaluation of the registration framework involved in template generation and mapping. A method for registration quality assessment enables the automatic detection of registration errors, and a semi-automatic registration method allows one to correct registrations, which is a prerequisite for a high-quality, curated database of expression patterns. All computational methods are available within the larvalign software package: https://github.com/larvalign/larvalign/releases/tag/v1.0.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Drosophila melanogaster; elastix; Gene expression patterns; Image registration; Larval brain; Standard brain